Contemplative Life amidst Mass Extinction: Catholic Revisions of Spirituality, Law, and Multispecies Justice - Willis Jenkins (Journal of Contemplative Studies)
Contemplative ecologies seem to face two liabilities of injustice. First, they may appear to seek spiritual satisfaction in multispecies relations without connection to political work to protect them from extinction. Yet addressing that liability may compound the second: that in a time of radically unequal exposure to Anthropocene stresses, extending protections of justice to nonhuman creatures may further erode aspirations for equal protection of human dignity. This essay examines how Contemplative Ecology may matter for multispecies justice by following Pope Francis’s attempt to redefine human dominion in contemplative terms for the sake of response to climate and extinction crises. That theological shift is accompanied by elevations of Indigenous governance rights and of rights for nature, although neither is endorsed fully or consistently. Ambiguities in this case can illuminate overarching questions about the relation of contemplative practice to ecological justice. Specifically, examining the uncertainties and liabilities in this case can aid inquiry into the role of contemplative practices within social and political transformations needed to repair relations with ecological systems.